Akad Salam Dalam Jual Beli Sayuran - Khusnudin, Imam; Rohman, Fatkhur; Annas, Muhamad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to: determine the implementation of the Salam Agreement on buying and selling in the hamlet of Connect Rejo, Bayu village, Songgon sub-district. This study uses a qualitative research method with the type of research case study research collected both the results of interviews, observations and documentation during conducting research in the hamlet of Connect Rejo, Bayu village, Songgon sub-district, using an interactive analysis model. The results of this study indicate that: The implementation of the salam contract on the sale and purchase of vegetables comes from several aspects, both from the farmers and the collectors themselves. The implementation of this salam contract is very beneficial for both farmers and collectors because they can know so far the practice of buying and selling is carried out according to or not with the provisions in the sale and purchase of the salam contract, namely with the concept of not being mutually beneficial to one party and mutual trust between farmers and collectors, therefore the author seeks to maximize this research so that it can help the community of Connect Rejo Hamlet, Bayu Village, Songgon District in practicing the buying and selling of vegetables that have long been carried out to meet the needs of family life, family and as their successors strive to be better in processing better vegetable crops so that they can develop the welfare of the life of the nation and the state It can be concluded that the implementation of the salam contract on the sale and purchase of vegetables in the Hamlet of Connect Rejo, Bayu Village, Songgon District, the identification of the implementation that occurs in the field, the measurement through the pillars and terms and has been practiced in the field, has gone through several long processes to form a thesis is in accordance with the provisions of the salam contract.